The effectiveness of experiential learning strategy to developing some fixed-case football plans for students - Ebrahim, Taher Yahya; Hussein, Saif Al-Haq Jasim Abdul (Universitas Tanjungpura, 2025)
Background and Study Aim. The rapid changes in various aspects of life require the optimal investment of mental potential and the building of a balanced personality in various aspects, especially since there is a need to develop the abilities of learners in all aspects to confront daily problems. The importance of the research was represented in constructing a scale of offensive skills and fixed-state plans in football for students, and realizing the relationship between them. Material and Methods. By creating two identical groups, the researchers employed the experimental technique. The sample consisted of thirty third-stage students from the University of Babylon's College of Physical Education and Sports Sciences, whereas the research community consisted of one hundred students. Results. The researchers also attribute the reasons for the differences in learning to the effect of using the (experiential learning) strategy, which is planning and implementing educational units, which facilitated the process of understanding the plans of the fixed offensive situations in modern football and absorbing them in their five sections (decision-making, implementation, movement, movement without the ball, coverage). Conclusions. There are statistically significant moral differences for the experiential learning strategy in creative thinking and some offensive situations and fixed-case plans in football for students. And also there are statistically significant moral differences for the experiential learning strategy in the development of some offensive situations in football for students.